Resistor-less Realization of Third-Order Quadrature Sinusoidal Oscillators Using CMOS VDIBAs - Komal, Ramnish Kumar, K. L. Pushkar (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
This article presents the two third-order sinusoidal quadrature oscillators (TOQSOs). These oscillators utilize three voltage differencing inverting buffered amplifiers (VDIBAs) along with three grounded capacitors (GCs), rendering them well-suited for integration within integrated circuits (ICs). The proposed configurations offer two quadrature voltage outputs. A significant advantage of these new oscillators is their self-regulating electronic control over both the condition of oscillation (CO) and the frequency of oscillation (FO). This control is achieved through separate transconductance elements for each oscillator. Moreover, the sensitivity analysis of FO concerning the active and passive components reveals that they exhibit low sensitivity. Another noteworthy feature of the presented oscillator designs is their low total harmonic distortion (THD), which enhances their overall performance. To validate the feasibility of these oscillators, PSPICE simulations have been conducted using 0.18um TSMC parameters, confirming their practicality and effectiveness.